Pre-Release Assessment for Javan Gibbon (Hylobates moloch) in The Javan Gibbon Center, Mount Gede Pangrango National Park - Anton Ario; Agus Priyono Kartono; Lilik Budi Prasetyo; Jatna Supriatna (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Preparation for gibbons before being released into their habitat is crucial. Thus, there is a need for readiness assessment of Javan gibbon with several criteria derived from other species of gibbons to determine individual readiness. Pre-release assessment study for Javan gibbon (Hylobates moloch) had been conducted in January – February 2014, November – December 2014, and March-April 2016 in the Javan Gibbon Center, Mount Gede Pangrango National Park, West Java, Indonesia. The objective of this research was to assess the readiness of Javan gibbon behavior prior to release. Data collection was conducted by focal animal sampling method with 5-minute interval recording time and ad libitum method. The average time allocations of Javan Gibbon activities were as follow: feeding (18.17±3.34%); moving (22.34±0.53%); resting (46.24±3.84%); socializing (10.13±4.33%); sexual activity (0.59±0.58%); and vocalizing (2.54±0.88%). The similarities of activity allocation from this study compared by wild Javan gibbons data found as follows: feeding by 33.03%, moving by 90.97%, resting by 61.52%, socializing by 38.09%, vocalizing by 75.02%, and sexual by 44.24%. Based on readiness assessment of 11 Javan gibbons, 3 individuals were considered almost ready for release, while 8 individuals were considered ready. The assessment of behaviors criteria for the readiness of Javan gibbons before release has not existed before. The results of this research are important as a recommendation for the management of wildlife rehabilitation and as a guideline in implementing the rehabilitation and reintroduction program of Javan gibbons.